The impact of green innovation practices on enhancing sustainable competitive advantage in Iraq - Ziber, Hiyam Hasan; Alabadi, Hashim Fawzi (Technium Business and Management, 2025)
To achieve the research goal, which is to diagnose and analyze the relationship between green innovation practices (in production and operations) and sustainable competitive advantage in the clothing factory, a hypothetical research model was developed that reflects the nature of the relationship and its impact on its variables. The research relied on the questionnaire, which made it the main tool for collecting data. The information was distributed to a sample of (86) employees and was tested using some statistical data tools. The study reached a number of points, the most important of which is that the exercise of obligations linked to the experience of a moral influence on the participants’ subscriptions is prominent in the obligations’ subscriptions, and confirms the obligations in production, and since a number of proposals were previously presented, the most important of which confirms this is the management of the garment factory by paying attention to green practices through... Conducting important green exercises to highlight the importance of concepts and standards that interrupt the environmental orientation that has become one that seeks to achieve a specific desire.